Historical biogeography of Heteropterinae skippers via Beringian and post‐Tethyan corridors. (11th November 2020) - Toussaint, Emmanuel F. A.; Ellis, Emily A.; Gott, Riley J.; Warren, Andrew D.; Dexter, Kelly M.; Storer, Caroline; Lohman, David J.; Kawahara, Akito Y.
Abstract: Skippers are a species rich and widespread group of butterflies with evolutionary patterns and processes largely unstudied despite some recent efforts. Among Hesperiidae, the subfamily Heteropterinae is a moderately diverse clade comprising ca. 200 species distributed from North to South America and from Africa to the Palearctic region. While some regions are species rich, others are far less diverse. Using anchored phylogenomics, we infer a robust timetree and estimate ancestral ranges to understand the biogeographic history of these skippers. Inferences based on up to 383 exons recover a robust backbone for the subfamily along with the monophyly of all genera. Bayesian divergence time estimates suggest an origin of Heteropterinae in the late Eocene, ca. 40 million years ago. Maximum likelihood ancestral range estimates indicate an origin of the group in the New World. The eastern Palearctic was likely colonized via a Beringian route and a reverse colonization event resulted in two independent and extant American clades. We estimate a vicariant event between Central and South America that significantly predates estimates of the proto‐Caribbean seaway closure, indicating active overwater dispersal in the Oligocene. The colonization of Africa from the east Palearctic is synchronous with the closure of the Tethys Ocean, while the colonization of Madagascar appears to be comparatively recent. Our results shed light on the systematics and biogeography of Heteropterinae skippers and unveil the evolutionary history of a new leaf in the skipper tree‐of‐life.